Research priorities in bronchiectasis. Issue 7 (15th December 2012) - De Soyza, Anthony; Brown, Jeremy Stuart; Loebinger, Michael R; ,
Abstract : Taking a network approach, we have identified research priorities in non-cystic fibrosis bronchiectasis. We discuss these in the context of increasing recognition of bronchiectasis and increasing mortality rates.